The kinetics of amylobarbitone metabolism in healthy men and women - Balasubramaniam, K. (1970)
1. Sodium amylobarbitone (3·54 mg/kg) was given by intravenous injection to seven healthy men and nine healthy women who were not receiving other drugs. Serum amylobarbitone and urine hydroxyamylobarbitone concentrations were measured by gas-liquid chromatography. There was no significant difference between the groups either in the serum amylobarbitone concentration/time curves or in the urinary excretion of hydroxyamylobarbitone. 2. The serum amylobarbitone concentration decayed over 48 h as a double exponential function of time; the first exponential component had a mean half-time of 0·6 h (males 0·56 ± 0·06 h, females 0·62 ± 0·08 h, ± S.E.) and the second exponential component had a mean half time of 21 h (males 22·7 ± 1·6 h, females 20·0 ± 1·0 h, ± S.E.). 3. The urinary excretion of hydroxyamylobarbitone over 48 h accounted for 34% of the dose (males 33·8 ± 3·2%, females 35·2 ± 3·0%, ± S.E.). One male and two female subjects excreted hydroxyamylobarbitone partly as a conjugate which was readily hydrolysed in acid. 4. An elimination constant (k(el)) derived from the serum concentration/time curve by the application of a two compartment model was approximately proportional to β (h(-1)), the rate constant of the second exponential component. There was a positive correlation (r=0·78, P<0·001) between β and the mean rate of urinary excretion of hydroxyamylobarbitone during the 24 to 48 h period.